PENGEMBANGAN ATRAKSI WISATA JELAJAH KINAHREJO BERBASIS KOMUNITAS - Retnaningtyas Susanti (JURNAL NASIONAL PARIWISATA, 2013)
This study has three main objectives: first, which describes existing and potential efforts by the community to develop a tourist attraction roaming Kinahrejo. Second, the mechanism for participation and management cruising Kinahrejo by the community. Third, the continuity of tourist attractions that can be seen roaming Kinahrejo from the economic, environmental, and social aspects. These three objectives are then combined to get an overview of post conditions Kinahrejo tourism Merapi eruption in 2010.This research was conducted with a qualitative descriptive method that provides an overview of the condition of the field based on observations and interviews at the informants had done. Data collection was conducted in an area attraction Roaming Kinahrejo and shelter as the residence of the offender Kinahrejo Cruising tourism, in addition to supporting data as for observation and interviews in the form of photo clarify the picture of the field, while the interviews were conducted to informants who are considered to have knowledge of Kinahrejo, disasters and tourist attractions Kinahrejo Roaming. Local knowledge possessed local communities is the key to this research.Development of a community-based tourist attraction efforts by Kinahrejo community that aims to get welfare in terms of economic, environmental, and social life. Therefore, to achieve these objectives cannot be separated from the management mechanism and the participation of the community joined in Kinahrejo. Tourist attractions Roaming Kinahrejo emerged as a form of resurrection after the disaster that evolved into a new source of livelihood for the people.